DEMAND FORECASTING IN THE MARITIME INDUSTRY, A CASE OF MAERSKLINE GHANA - Mensah, John; Anim, Stephen Kwasi (Archives of Business Research, 2016)
Demand forecasting is of critical essence to the maritime industry, especially in Ghana. On this note the study sought to achieve among other things by identifying the type(s) of model(s) used by Maritime industry in forecasting their operational demands as well as develop an appropriate forecasting model(s) for these industry using Maersk line as a case study. We realized that Maersk line preferred to be responsive and as such incur more cost by underutilizing their capacity. Maersk line Ghana should not use only one model to forecast for both exports and import data. We therefore recommend from our study that the organization should use exponential smoothing model of forecasting to forecast their export data only.